Quantitative Proteomics Analysis Reveals That Cyclooxygenase-2 Modulates Mitochondrial Respiratory Chain Complex IV in Cardiomyocytes - Alvarez, Maria Soledad (2022)
The biochemical mechanisms of cell injury and myocardial cell death after myocardial infarction remain unresolved. Cyclooxygenase 2 (COX-2), a key enzyme in prostanoid synthesis, is expressed in human ischemic myocardium and dilated cardiomyopathy, but it is absent in healthy hearts. To assess the role of COX-2 in cardiovascular physiopathology, we developed transgenic mice that constitutively express functional human COX-2 in cardiomyocytes under the control of the α-myosin heavy chain promoter. These animals had no apparent phenotype but were protected against ischemia-reperfusion injury in isolated hearts, with enhanced functional recovery and diminished cellular necrosis. To further explore the phenotype of this animal model, we carried out a differential proteome analysis of wild-type vs. transgenic cardiomyocytes. The results revealed a tissue-specific proteomic profile dominated by mitochondrial proteins. In particular, an increased expression of respiratory chain complex IV proteins was observed. This correlated with increased catalytic activity, enhanced respiratory capacity, and increased ATP levels in the heart of COX-2 transgenic mice. These data suggest a new link between COX-2 and mitochondria, which might contribute to the protective cardiac effects of COX-2 against ischemia-reperfusion injury.